2011
DOI: 10.1111/j.1600-0722.2011.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of candidate genes and cleft lip and palate taking into consideration geographical origin

Abstract: Isolated cleft lip and/or palate (CL/CLP) is a complex congenital anomaly with many contributing factors. There are several genes involved in the aetiology of CL/CLP, they are different in selected populations. In a previous study, the mitochondrial haplotypes of Latvian subjects with CL/CLP were characterized. Latvian subjects with CL/CLP have mostly mitochondrial haplogroups U4/U5 compared with the ethnic population of Latvia. The aim of this study was to stratify the results of genotyping based on European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
7
0
8
Order By: Relevance
“…The craniofacial development involves a series of highly coordinated events, including proliferation, migration, epithelial-mesenchymal transition, and apoptosis, and polymorphic variations in genes that control these events may affect the normal development of the lips and palate, resulting in NSCL/P (Butali et al, 2011). Previous studies have shown statistical evidences of association between specific genes, including transition nuclear protein 1 ( TNP1 ; Beaty et al, 2006), muscle segment homeobox 1 ( MSX1 ; Beaty et al, 2002; Vieira et al, 2003; Suazo et al, 2004; Jagomagi et al, 2010; Nikopensius et al, 2010; Butali et al, 2011; Cardoso et al, 2013), Treacher Collins-Franceschetti syndrome 1 ( TCOF1 ; Masotti et al, 2005; Sull et al, 2008), fibroblast growth factor receptor 1 ( FGFR1 ; Menezes et al, 2008; Nikopensius et al, 2010; Lace et al, 2011), collagen type II, alpha 1 ( COL2A1 ; Nikopensius et al, 2010), wingless-type MMTV integration site family, member 3 ( WNT3 ; Chiquet et al, 2008; Nikopensius et al, 2010; Lace et al, 2011; Mostowska et al, 2012), tissue inhibitor of metallopeptidase 3 ( TIMP3 ; Nikopensius et al, 2010), and nonsyndromic oral clefts across different populations. However, the involvement of these genes in the Brazilian population remains uncertain.…”
mentioning
confidence: 99%
“…The craniofacial development involves a series of highly coordinated events, including proliferation, migration, epithelial-mesenchymal transition, and apoptosis, and polymorphic variations in genes that control these events may affect the normal development of the lips and palate, resulting in NSCL/P (Butali et al, 2011). Previous studies have shown statistical evidences of association between specific genes, including transition nuclear protein 1 ( TNP1 ; Beaty et al, 2006), muscle segment homeobox 1 ( MSX1 ; Beaty et al, 2002; Vieira et al, 2003; Suazo et al, 2004; Jagomagi et al, 2010; Nikopensius et al, 2010; Butali et al, 2011; Cardoso et al, 2013), Treacher Collins-Franceschetti syndrome 1 ( TCOF1 ; Masotti et al, 2005; Sull et al, 2008), fibroblast growth factor receptor 1 ( FGFR1 ; Menezes et al, 2008; Nikopensius et al, 2010; Lace et al, 2011), collagen type II, alpha 1 ( COL2A1 ; Nikopensius et al, 2010), wingless-type MMTV integration site family, member 3 ( WNT3 ; Chiquet et al, 2008; Nikopensius et al, 2010; Lace et al, 2011; Mostowska et al, 2012), tissue inhibitor of metallopeptidase 3 ( TIMP3 ; Nikopensius et al, 2010), and nonsyndromic oral clefts across different populations. However, the involvement of these genes in the Brazilian population remains uncertain.…”
mentioning
confidence: 99%
“…As a result authors conclude that it is unlike that mtDNA has a direct role in cleft lip and palate predisposition [37]. Therefore all newborns and their parents should be closely evaluated, examined and had special data gathered, which might be very useful in diagnosis and prevention of orofacial clefts.…”
Section: Family History and Genetic Factorsmentioning
confidence: 99%
“…Two most common types of CLP are cleft lip with or without cleft palate and a cleft palate only [1]. This condition reflects a breakdown in normal embryological facial development which 70% affects the upper lip, the alveolar ridge, tooth eruption and palate fusion [6][7]. Another 30% clefts are caused by monogenic syndromes or chromosomal aberrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…This condition reflects a breakdown in normal embryological facial development which 70% affects the upper lip, the alveolar ridge, tooth eruption and palate fusion [6][7]. Another 30% clefts are caused by monogenic syndromes or chromosomal aberrations [7]. This cleft lip and palate caused major psychosocial and economic burden for families and society that usually require surgical repair [8][9].…”
Section: Introductionmentioning
confidence: 99%